TEACHER'S PROFILE AS AN AGENT OF CHANGE IN PREPARING SCHOOL AND PEOPLE AT THE NEW NORMAL ERA - Memet Casmat; Andayani Andayani (Universitas Pendidikan Indonesia, 2022)
In the Covid-19 Pandemic, the teacher's role is not only as a teacher in a formal school but is expected to be an agent of renewal in the face of a new normal where we must all be able to live with the coronavirus. This research aims to understand teachers' experiences as community coaches or extensions and the most appropriate type of training during this pandemic. The data in this descriptive study was obtained from the spread of questionnaires to 16,546 respondents who were teachers at the early childhood education (PAUD) to high school (SMA) levels throughout Indonesia. Data processing and analysis were done descriptively and obtained some results. Notably, 77.8% of respondents have experience in providing training, and the most training materials ever given by teachers as coaches are about education, which is 88.9%. Related to the skills needed to act as a coach with material about life in the Era New Normal, most teachers assume that speaking in public, developing presentation materials, and using technology are skills that must be possessed. Furthermore, the study's results can be a reference for developing training forms with teachers as coaches or extensionists, especially in the New Normal era.